Group portrait of the attendees of the 1939 Mount Hermon Northern California Baptist Youth Movement Bible Conference - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of the attendees of the 1939 Northern California Baptist Youth Movement Bible Conference, held July 1939 at Mount Hermon, California.